Efek Variasi Penambahan Carbomer Terhadap Nilai pH, Viskositas dan Aktivitas Mikroba Pada Sediaan Hand Sanitizer - Putri , Melysa; Hafnimardiyanti , Hafnimardiyanti; Savitri , Dian (REACTOR: Journal of Research on Chemistry and Engineering, 2021)
Hand sanitizer is an antiseptic in gel form. The gel texture in hand sanitizers is caused by the carbomer which acts as a gelling agent. Therefore, this research was done to observe the effect of carbomer on the value of pH, viscosity, and microbial activity in hand sanitizers. As for testing pH using pH meters, testing viscosity was carried out using the viscometer method, while microbial activity was carried out using the Total Plate Number, Yeast Mold Number and microbial pathogen tests. Based on the data obtained, the carbomer greatly influences the increase in the viscosity of the hand sanitizer gel, the pH value was obtained at 6.0 - 7.06, while in the microbial activity test none of the microbes grew in each medium. Therefore, it can be concluded that the hand sanitizer with code P3 is the best sample